Assessment of Pattern, Severity and Outcome of Poisoning in Emergency Care Unit - Eswaran Maheswari, Lydia Abraham, Chinju Susan Chacko, Ganesan Rajalekshmi Saraswathy, Aruna Chala Ramesh (Journal of Applied Pharmaceutical Science, 2016)
The current study was a prospective observational study. All poisoning cases admitted in the emergency care unit of M.S. Ramaiah Hospital and Memorial Hospital were included in the study. A total of 101 patients were included in the study. The pattern, severity and outcome of poison case were assessed using suitable scales. The common agent involved in poisoning was drugs. It accounted for 38.60% of total poisoning cases. This was followed by organophosphorous (OP) compounds, corrosive agents, rat poison, bedbug solutions and insecticides. According to APACHE II the estimated mortality was found to be 10.71. The mean Glasgow coma scale was 13.75±2.25. Out of 101 patients, 100 (99.01%) recovered and 1 (0.99%) died. Analysis of 101 poison cases revealed that most poisonings are due to over dose of drugs and also due to consumption of OP compounds. Establishment of strict policies against the sale and availability of agriculture field products and over the counter drugs are an effective way to control OP and drug poisoning. Accidental poisoning by paediatric groups can be minimized by conducting educational programs for the population in the rural regions.
Keywords: Poison; Severity, Organophosphorous, Glasgow coma scale, APACHE II.